Toshiba v Commission: Court of Justice Eases Burden on Commission to Fine Parent Companies for Competition Law Infringements by Joint Ventures. (21st March 2017) - MacLennan, Jacquelyn; Kadri, Aqeel
Abstract: Case C-623/15 P Toshiba v Commission EU:C:2017:21 The Court of Justice confirms that companies with minority stakes in joint ventures are at risk of liability even where they play a minor role in the management of the joint venture.